Triple Threat: Three Primary Malignancies Simultaneously Involving Three Genitourinary Organs. (17th April 2023) - Mitchell, Katharina; El Naili, Reima; Pillai, Lakshmikumar; Lopez, Eric Mark; Riordan, John; Marsh, Wallis; Luchey, Adam; Hajiran, Ali
Abstract : Statistically, the chance of having concurrent renal cell carcinoma (RCC), urothelial carcinoma of the bladder (UC), and a neuroendocrine tumor (NET) of the renal parenchyma is less than one in a trillion. Herein, we describe an unusual case of a 67-year-old female who presented with bilateral flank pain and severe gross hematuria. Cross-sectional imaging revealed two large heterogeneous, endophytic renal masses with a single enlarged paracaval lymph node. Diagnostic cystoscopy was performed for completion of gross hematuria evaluation and revealed a concurrent papillary bladder tumor. Percutaneous biopsies of bilateral renal masses revealed clear cell RCC involving the left kidney and well-differentiated NET involving the right kidney, and transurethral resection of the bladder tumor revealed high-grade nonmuscle invasive urothelial carcinoma. The patient elected to undergo bilateral nephroureterectomy, radical cystectomy, and retroperitoneal and pelvic lymphadenectomy. Final pathology confirmed the presence of three different malignancies: noninvasive high-grade papillary UC of the bladder (pTaN0), left renal clear cell RCC (pT2bN0), right renal well-differentiated NET, and a single paracaval lymph nodes positive for metastatic NET (pT2aN1).